2015
DOI: 10.3390/molecules201017929
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid-Based Ultrasonic-Assisted Extraction of Secoisolariciresinol Diglucoside from Flaxseed (Linum usitatissimum L.) with Further Purification by an Aqueous Two-Phase System

Abstract: Abstract:In this work, a two-step extraction methodology of ionic liquid-based ultrasonic-assisted extraction (IL-UAE) and ionic liquid-based aqueous two-phase system (IL-ATPS) was developed for the extraction and purification of secoisolariciresinol diglucoside (SDG) from flaxseed. In the IL-UAE step, several kinds of ILs were investigated as the extractants, to identify the IL that affords the optimum extraction yield. The extraction conditions such as IL concentration, ultrasonic irradiation time, and liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The screening effect of the IL anion on its extraction efficiency for analytes is considered to be a critical factor, and has significant effects [24,25]. In this study, the 1-butyl-3-methylimidazolium ILs with six different classes of anions (Br − , BF 4 − , OAC − , PF 6 − , Cl − , NO 3 − ) were evaluated, and the differences for TBF content were readily evident.…”
Section: Resultsmentioning
confidence: 99%
“…The screening effect of the IL anion on its extraction efficiency for analytes is considered to be a critical factor, and has significant effects [24,25]. In this study, the 1-butyl-3-methylimidazolium ILs with six different classes of anions (Br − , BF 4 − , OAC − , PF 6 − , Cl − , NO 3 − ) were evaluated, and the differences for TBF content were readily evident.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that phase forming ability of ILs increased with the increase in their hydrophobicity. That is, the hydrophobicity of ILs is beneficial to the formation of ATPS [ 3 , 87 , 88 ]. On the other hand, the property of salts has an influence on the phase formation process.…”
Section: Mechanism Of Phase Separationmentioning
confidence: 99%
“…Extraction of pharmaceutical molecules (active ingredients or intermediates) is often from plant materials. The isolation of high purity secoisolariciresinol diglucoside, a multi-functional pharmaceutical, from flaxseed, was simplified and improved with an ultrasonic-assisted extraction followed by IL-ATPS formation by the addition of Na 2 SO 4 (Tan et al, 2015 ). A similar example where fractionation and recovery of bioactive hydroxycinnamic derivatives from stressed carrot mass using IL-ATPS formed from [emim]acetate/potassium buffers gave a different phenolic ratio than conventional ATPS (Sánchez-Rangel et al, 2016 ).…”
Section: Il Extractionsmentioning
confidence: 99%